Violence against women during coronavirus: when staying home isn't safe - Pfitzner, Naomi (Palgrave pivot, 2023)
1. Contextualising COVID-19: DFV and times of crisis -- 2. The ‘shadow pandemic’: domestic and family violence during COVID-19 -- 3. The plight of temporary migrants: temporariness and family violence support -- 4. In the shadow of COVID: The invisibility of children’s experiences of violence in homes during the pandemic -- 5. The Pandemic Pivot: DFV service innovation and remote delivery during COVID-19 restrictions -- 6. Justice in lockdown -- 7. #WFH: worker wellbeing during the ‘shadow pandemic’ -- 8. Conclusion: Building back safer for women and children.